Đánh giá thực trạng rèn kĩ năng giao tiếp của sinh viên tại các câu lạc bộ ở Trường Đại học Hùng Vương - Bùi, Thị Loan (Tạp chí Giáo dục, 2024)
One of the best ways to develop communication skills for students is through club activities. Based on theoretical research, the article evaluated the current situation of training communication skills for Hung Vuong University students at clubs. The research was conducted on 45 lecturers and 1,525 students at Hung Vuong University in 9 specialized faculties with many different methods and forms of assessment. The results show that the communication skills of students at the clubs are generally at a good level. Among them, students of the Faculty of Economics are considered to be the faculty with the best results in training communication skills in the school, followed by students of the Faculty of Primary Education and Early Childhood Education and the Faculty of Foreign Languages. However, the difference in communication skills assessment results in the three faculties is generally not much. On the other hand, the article also evaluated the advantages and disadvantages of students in the process of practising communication skills at clubs. This is an important practical basis for the article to continue to propose some measures to improve the quality of communication skills for students at Hung Vuong University.